Guinea- Bissau : Selected Issues Paper. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper explains the cashew economy and the unfolding of the 2017 campaign. At least half of all households are thought to be engaged in production, commercialization, or exportation of cashew nuts. The activity has at least four macroeconomic impacts: one, it injects liquidity to producers; two, owing to producers' high propensity to consume, it impacts the price level; third, it is the main provider of foreign exchange via exports; and fourth, it is an important source of fiscal revenues. Despite streamlining of marketing arrangements over the years, cashew production is still subject to significant government intervention. Vested interests have traditionally permeated public policies, with nontransparent issuance of licenses and permits used in some instances to block competition. Cashew production started to expand during the 1980s and yearly output has over the years increased to currently about 200,000 tons. Native of north Brazil, cashew trees were introduced by the Portuguese during the colonial period but output remained negligible through to the country's independence in 1973.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet